2016
DOI: 10.4236/acs.2016.62025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rainy Season Onset, Cessation and Duration for Ghana from RegCM4 and GMet Datasets

Abstract: The socio-economic sector of West African countries is rain-fed agriculture driven. Information regarding the onset, cessation and duration of the rainy season is thus, very essential. In this paper, a comparison of the onset, cessation and duration of the rainy season has been carried out using simulated rainfall data from the fourth generation Regional Climate Model (RegCM4) and rain gauge measurements from Ghana Meteorological Agency (GMet), covering a period of 1998 to 2012. Similar onset and cessation dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…() and Mensah et al . () were used to assess the performance of GMet v1.0. These statistical metrics include Pearson's correlation coefficient, bias and root mean squared error (hereafter termed as rmse), given in Equations – as: rxy=i=1N()xiμx0.5em()yiμy()N10.5emSxSy bias=1N()xiyi rmse=1i=1Nyixi2i=1Nxiμx2 …”
Section: Methodssupporting
confidence: 85%
See 4 more Smart Citations
“…() and Mensah et al . () were used to assess the performance of GMet v1.0. These statistical metrics include Pearson's correlation coefficient, bias and root mean squared error (hereafter termed as rmse), given in Equations – as: rxy=i=1N()xiμx0.5em()yiμy()N10.5emSxSy bias=1N()xiyi rmse=1i=1Nyixi2i=1Nxiμx2 …”
Section: Methodssupporting
confidence: 85%
“…Seasonal analysis of both GMet v1.0 and GPCC captured DJF (December–January–February) as the driest period over the entire country, with a rainfall total below 300 mm (see Figures (a)–(f)). Similar to findings in Owusu and Waylen (), Amekudzi et al () and Mensah et al (), the MAM (March–April–May) season was observed to be the rainfall onset period for all four agro‐ecological zones (see Figures (b)–(g)), which is attributable to the northward migration of the tropical rainbelt (N'Tchayi Mbourou et al, ; Sultan and Janicot, ; Flamant et al, ; Nicholson, ). Within this season, suspected heightening in solar activity (Chakraborty and Bandyopadhaya, ) over the zones leads to the generation of more convective systems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations